The counseling process : a multitheoretical integrative approach - Welfel, Elizabeth Reynolds; Patterson, Lewis E. (Belmont, Calif. : Thomson Brooks/Cole, 2005)
Intended for graduate or advanced undergraduate students, this textbook for a counseling methods course outlines the process of identifying the issues a client faces, illuminating their causes, and developing an action plan to alter emotions, thoughts, and behaviors. The sixth edition expands some later sections on incorporating diversity, counseling men and boys, and working with older adults. Annotation : 2004 Book News, Inc., Portland, OR (booknews.com
Ch. 1. Ch. 2. Ch. 3. Ch. 4. Ch. 5. Ch. 6. Ch. 7. Ch. 8. Ch. 9. Ch. 10. Ch. 11. Ch. 12. Ch. 13. Ch. 14. App. A. App. B. App. C. App. D.
Includes bibliographical references and indexes.
Keywords: Counseling